Parietal cell hyperplasia induced by long-term administration of antacids to rats. Issue 9 (September 1978) - Mazzacca, G; Cascione, F; Budillon, G; D'Agostino, L; Cimino, L; Femiano, C
Abstract : Suspension of magnesium and aluminum hydroxide (30--60 mEq/24h) or a comparable volme of water was orally administered by gastric intubation to two groups of 20 male Wistar rats each over 60 days. The antacid treatment led to a significant increase in the height (0.464 +/- 0.02 mm v. 0.318 +/- 0.06) and in the volume (472 +/- 32 mm3v.328 +/- 45) of the fundic mucosa of the stomach, in the average count of parietal cells per unit area of the mucosa (32.37 +/- 1.8 v. 22.3 +/- 1.6), and in the total parietal cell population of the stomach (53.6 +/- 3.5 x 10(6) v. 43.2 +/- 3.7 x 10(6)). Furthermore fasting serum gastrin concentration was significantly higher in the antacid treated rats (81.2 +/- 7.4 pg/ml) than in control animals (56.9 +/- 6.9 pg/ml).